The prognostic value of stem cell markers in triple-negative breast cancer - Almási Szintia; Nagy Ágnes; Krenács Tibor; Lantos Tamás; Zombori Tamás; Cserni Gábor (2023)
Among the many consecutive theories of cancer, the stem cell theory is currently the most accepted one. Cancer stem cells are located in small niches with specific environment, renew themselves and are believed to be responsible for many recurrences. They can be highlighted with stem cell markers, but often these markers also label tumor cells, and this may represent a phenotypical change associated with prognosis. In this study, we attempted to match tumor outcomes with the expression of the following stem cell markers: ALDH1, AnnexinA1, CD44, CD117, CD166, Nanog and oct-4. Tissue microarray blocks from triple-negative breast cancers were immunostained for the listed markers, and their expression by the majority of tumor cells (diffuse positivity) was correlated with prognosis. Of the 106 tumors investigated, diffuse positivity was seen in 7 (ALDH1), 33 (AnnexinA1), 53 (CD44), 44 (CD117 membranous only), 49 (CD117), 72 (CD166), 19 (Nanog), and 11 (oct-4) cases. With a median follow-up of 83 months, ALDH1 and CD117 expression was associated with DFS, whereas CD44, CD117 and CD166 were associated with OS estimates, based on Kaplan-Meier analyses. In the multivariate Cox proportional hazard models (including the examined markers and clinicopathological data which had a statistical impact in the univariate analysis), the pN category and the lack of ALDH1 expression were independent prognosticators for DFS, and the pN category and diffuse CD44 staining were independent prognosticators for OS. In the multivariate analysis including all of the examined clinicopathological data and markers, only CD117 showed a statistical impact on OS. We failed to demonstrate a prognostic impact for most stem cell markers tested in triple-negative breast cancer, but lack of ALDH1 staining and CD44 expression appears as of prognostic value, requiring further examination in independent studies.
Keywords: Klinikai orvostan